2006
DOI: 10.1111/j.1464-410x.2006.06379.x
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of positive biopsy cores, preoperative prostate‐specific antigen (PSA) level, pT and Gleason score as predictors of PSA recurrence after radical prostatectomy: a multi‐institutional outcome study in Japan

Abstract: were collected from the Urological Oncology Study Group, a subgroup of Japan Clinical Oncology Group. RESULTSThe patients' median (range) age was 67 (47-83) years and their PSA level before RP was 8.7 (1.0-153) ng/mL. During the median follow-up of 45.6 months, 302 of the 1192 patients (25.3%) developed PSA recurrence. The median time to recurrence was 369 (61-2128) days after RP. A log-rank test showed that five significant clinicopathological factors were associated with PSA recurrence after RP: The percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…When measured in the RP specimen, the expression of VEGF‐A could help to identify patients at high risk of tumour recurrence. Currently the main postoperative factors that predict the risk of recurrence are the Gleason score, the pathological stage, and the surgical margin status [11,12]. VEGF‐A expression in the RP specimen could be an additional factor for predicting outcome; it could be considered before indicating an adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…When measured in the RP specimen, the expression of VEGF‐A could help to identify patients at high risk of tumour recurrence. Currently the main postoperative factors that predict the risk of recurrence are the Gleason score, the pathological stage, and the surgical margin status [11,12]. VEGF‐A expression in the RP specimen could be an additional factor for predicting outcome; it could be considered before indicating an adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year progression-free, and biochemical relapse-free survival rates according to the risk group were 100%, 90.8% in the low-risk group, 98.3%, 75.7% in the intermediate-risk group and 93.6%, 67.6% in the high-risk group. 100 The author also mentioned that the survival result is comparable to T1-T2 patients who had a radical prostatectomy in Japan, 101 indicating that EBRT is a promising option in low and intermediate risk patients in Asia. However, consensus has not been reached on the practice and management of postoperative RT for patients with Prostate cancer in Japan yet.…”
Section: Treatmentmentioning
confidence: 99%
“…These results suggest that the detection of prostate cancer at a repeat biopsy does not predict a favorable outcome. Rather, several studies have indicated that the number or percentage of positive biopsy cores may be an important predictor of a favorable outcome [ 4 - 7 ].…”
Section: Introductionmentioning
confidence: 99%